From worldly bondage to Nirvana in Jainism: Jain Dharm Me Sansarik Trashna-Bandhan se Nirvan Ki Or - Dr. Rakhi Kaushik (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
In Jainism, the world is considered to be sad. Man suffers from Jara (old age) and death. A person is surrounded by the desires of worldly life. Along with the accumulation of wealth, the thirst in the form of human desires increases, which has no end. Lust is like a poison that ultimately gives rise to unhappiness. Renunciation of the world and renunciation can only lead a person towards true happiness and helps in attaining Nirvana